Studies of Values Conducted by Vladimir Yadov and His Colleagues - Николай Иванович Лапин (Journal of Economic Sociology, 2010)
Published by Yadov’s anniversary,  an especial collection “Vivat, Yadov!” contains his colleagues’  memories and thoughts. The presented paper focuses on the Yadov’s research which is considered to be his main contribution into the sociological theory – on contradictions between individual value orientations and observed behavior. Those studies resulted in a book titled “Self-regulation and Prediction of Social Behavior of Individuals” (1979), suggesting an assumption of hierarchical structure of personal dispositions, of this structure’s social bases and its systematic inﬂ uence on observed behavior.  This paper is devoted to Prof. Yadov and his colleagues but it also presents a review on Russian works on value studies.